Leptogenesis in \(A_4\) Flavor Symmetry Model by Renormalization Group Evolution - Phong, Nguyen Thanh (Communications in Physics, 2014)
We study how leptogenesis can be implemented in the seesaw models with \(A_4\) flavor symmetry, which lead to the tri-bimaximalneutrino mixing matrix. By considering renormalzation groupevolution from a high energy scale of flavor symmetry breaking(the GUT scale is assumed) to the low energy scale of relevantphenomena, the off-diagonal terms in a combination of DiracYukawa-coupling matrix can be generated. As aresult, the flavored leptogenesis is successfully realized. Wealso investigate how the effective light neutrino mass \(|\langle m_{ee}\rangle |\) associated with neutrinoless double beta decaycan be predicted byimposing the experimental data on the low energy observables. Wefind a link between the leptogenesis and the neutrinoless doublebeta decay characterized by \(|\langle m_{ee}\rangle|\) through ahigh energy CP phase $φ$, which is correlated with the lowenergy Majorana CP phases. It is shown that the predictions of \(|\langle m_{ee}\rangle|\) for some fixed parameters of the highenergy physics can be constrained by the current observation ofbaryon asymmetry.